STUDI HUBUNGAN ANTARA pH, ALUMINUM DAPAT TUKAR, DAN KADAR P-TERSEDIA PADA TANAH ULTISOL DENGAN PEMBERIAN KOMPOS AMPAS SAGU - ANAS, ARSY AYSYAH; ARMA, MAKMUR JAYA; HISEIN, WAODE SITTI ANIMA (Jurnal Agroteknos, 2024)
This research aimed to examine the relationship between soil pH, exchangeable aluminum (Al-dd), and available phosphorus (P-available) in Ultisol soil through the application of sago waste compost. The research was conducted in a greenhouse located in Wowawanggu Village, Kadia District, Kendari City. Soil analysis was performed at the Laboratorium Dasar Kimia Analitik, Haluoleo University. The study was designed based on a Completely Randomized Design (CRD) with sago waste compost treatment doses, where each treatment was repeated 3 times. The doses of sago waste compost tested consisted of three levels: 10 tons/ha (KAS1), 20 tons/ha (KAS2), and 30 tons/ha (KAS3). Soil analysis was conducted on pH, Al-dd, and P-available before and after the application of sago pulp compost. Observations after application were made in stages every 7 days with four observations. The results showed that the application of sago waste compost had a significant effect on increasing pH and P-available and decreasing Al-dd in Ultisol soil. There was a very strong relationship between pH, P-available, and Al-dd, as indicated by a correlation coefficient value of > 0.90. The best treatment was shown by KAS3, with a sago waste compost dose of 30 tons/ha.